Decoding PARP Inhibitor Resistance in Ovarian Cancer: Molecular Insights and Emerging Therapeutic Strategies - Meneses Rêgo, Amalia Cinthia; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2024)
Ovarian cancer remains one of the most lethal gynecologic malignancies, primarily due to its late-stage diagnosis and frequent relapse. Poly (ADP-ribose) polymerase (PARP) inhibitors have emerged as promising agents in the management of ovarian neoplasms, particularly among patients with BRCA1/2 mutations or homologous recombination deficiency (HRD). Despite initial therapeutic successes, the development of drug resistance poses a significant challenge, limiting the long-term efficacy of these agents. This review analyzes the molecular mechanisms underlying PARP inhibitor resistance, including genetic reversion mutations in BRCA1/2, restoration of homologous recombination repair pathways, and alterations in drug efflux mechanisms. Furthermore, we explore strategies to overcome PARP inhibitor resistance, such as combination therapies with other targeted agents, using ATR inhibitors, and optimizing the timing of maintenance chemotherapy. Current advances in identifying predictive biomarkers for PARP inhibitor response are also discussed, offering potential pathways for personalized treatment approaches. Understanding the complex interplay of resistance mechanisms and the evolving therapeutic landscape is crucial to improving outcomes in patients with ovarian cancer. This review aims to summarize current knowledge on PARP inhibitor resistance and emerging strategies to enhance their therapeutic potential in ovarian neoplasms.